2023
DOI: 10.6007/ijarped/v12-i1/15707
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of School Students' Environmental Knowledge, Attitude, Behavior, and Awareness toward the Environment: A Systematic Review

Abstract: The quality of the environment is thought to have deteriorated at an alarming rate. Hence environmental education and awareness become critical steps to mitigate the issue. The current paper attempts to undertake a Systematic Literature Review (SLR) that focuses on the student's knowledge, attitude, awareness, and behavior toward the environment to identify the relationship among these variables as well as the methods for improving the environment. The PRISMA Statement (Preferred Reporting Items for Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In sync with Marcinkowski and Reid (2019); Kanada et al (2022) have found that the TPB has a limited ability to predict behavior, particularly in complex or dynamic situations. Firmanshah et al (2023) also found that adopting the TPB fails to account for the role of emotions, such as fear or anxiety, which can also influence behavior.…”
Section: Factors Contribute To Technology Readinessmentioning
confidence: 99%
“…In sync with Marcinkowski and Reid (2019); Kanada et al (2022) have found that the TPB has a limited ability to predict behavior, particularly in complex or dynamic situations. Firmanshah et al (2023) also found that adopting the TPB fails to account for the role of emotions, such as fear or anxiety, which can also influence behavior.…”
Section: Factors Contribute To Technology Readinessmentioning
confidence: 99%